2011
DOI: 10.1099/ijs.0.028522-0
|View full text |Cite
|
Sign up to set email alerts
|

Weissella ceti sp. nov., isolated from beaked whales (Mesoplodon bidens)

Abstract: During an investigation into the microbiota of beaked whales (Mesoplodon bidens), nine isolates were obtained from different organs of four animals. The isolates were Gram-positive-staining, catalase-negative, short rod-shaped or coccoid organisms. A phylogenetic analysis based on 16S rRNA gene sequences of these isolates allocated them to the genus Weissella, showing 96.3 % and 96.0 % 16S rRNA gene sequence similarity with Weissella viridescens NRIC 1536 T and Weissella minor NRIC 1625 T , respectively. On th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 24 publications
0
37
0
Order By: Relevance
“…The trout isolates also show >99% 16S sequence similarity to W. ceti sp. nov., which was recently isolated from beaked whales (9), and therefore, the whale and fish isolates may constitute a single species. The occurrence of this pathogen on three continents over a relatively short period (5 years) suggests that weissellosis is a rapidly emerging disease of farmed rainbow trout.…”
Section: Genome Announcementmentioning
confidence: 99%
“…The trout isolates also show >99% 16S sequence similarity to W. ceti sp. nov., which was recently isolated from beaked whales (9), and therefore, the whale and fish isolates may constitute a single species. The occurrence of this pathogen on three continents over a relatively short period (5 years) suggests that weissellosis is a rapidly emerging disease of farmed rainbow trout.…”
Section: Genome Announcementmentioning
confidence: 99%
“…nov., isolated from stranded beaked whales (Vela et al . ). While these data suggested that the isolates may constitute a single species, further genomic and functional analyses (with additional W. ceti whale isolates) will be necessary to better understand the evolutionary relationships among these strains.…”
Section: Introductionmentioning
confidence: 97%
“…Species of this branch harbor diverse habitats. W. viridescens and W. halotolerans have been isolated from meat products [20,24], W. minor from milking machine sludge [20], W. ceti from a beaked whale [17] and W. uvarum from wine grapes [25].…”
Section: Taxonomical Position and Specific Traitsmentioning
confidence: 99%